COEXISTING IN HARMONY: THE ROLE OF TRI HITA KARANA PHILOSOPHY IN THE SOCIAL STRUCTURE OF BALINESE SOCIETY - Limas Dwi Lestari; I Wayan Kandia; I Gusti Ngurah Santika; Yustina Podu Bara; Franselin Melisa Syukur (CV. Tirta Pustaka Press, 2025)
This study investigates how the philosophy of Tri Hita Karana functions as an analytical framework for understanding the configuration of social relations in Balinese society. Addressing the research question—in what ways do the principles of Parhyangan, Pawongan, and Palemahan shape and regulate social structure amid contemporary sociocultural change?—the study employs a qualitative design grounded in interpretive sociology. Data were collected through purposive observations, semi-structured interviews with community leaders and cultural practitioners, and document analysis of local regulations and customary texts. Guided by the conceptual lens of relational ontology, the analysis demonstrates that Tri Hita Karana does not merely serve as a cultural value system but operates as a dynamic mechanism that structures authority, communal cooperation, and ecological stewardship. The findings reveal the adaptive capacities of these principles when faced with pressures from modernization, tourism development, and shifting land-use patterns. Rather than remaining static, the philosophy evolves through institutional innovations such as community-based agritourism, participatory land governance, and temple-centered social coordination. This study contributes theoretically by situating Tri Hita Karana within broader debates on indigenous knowledge systems and sustainable social organization. It also offers scholarly insight into how localized philosophical frameworks can generate resilient socio-ecological governance models.